Brain, mind, and developmental psychopathology in childhood - Garralda, M. Elena; Raynaud, Jean-Philippe, 1960- (IACAPAP book series, 2012)
"Brain, Mind, and Developmental Psychopathology in Childhood, part of the International Association of Child and Adolescent Psychiatry and Allied Professions' book series "Working with Children & Adolescents" edited by Elena Garralda and Jean-Philippe Raynaud updates the knowledge about connections between brain, mind, and developmental psychopathology. The volume illuminates our understanding of different types of psychiatric disorders in children including autism, hyperkinetic disorder, obsessive compulsive disorder, and childhood schizophreniaand the effects of child maltreatment and deliberate self harm. This book describes how to integrate physical and psychological treatments for child and adolescent mental health problems and advocacy for the treatment of children and adolescents with mental health problems. "--Provided by publisher.